The Influence of Organizational Culture, and Work Motivation on Employee Performance with Job Satisfaction as an Intervening Variable - Faturrahman, Satria; Yuniawan, Ahyar (JURNAL BISNIS STRATEGI, 2023)
This study investigates the critical link between human capital and organizational success by examining the influence of organizational culture and work motivation on employee performance. We hypothesize that job satisfaction plays a  mediating role in this interplay. Employing a quantitative approach with 90 respondents at Hotel Grandhika Pemuda Semarang, Indonesia, we analyze data using multiple linear regression. Our findings reveal a significant positive influence of both organizational culture and work motivation on job satisfaction. Furthermore, all three variables demonstrate a robust impact on employee performance. Notably, job satisfaction emerges as a significant mediator, underscoring its crucial role in translating positive organizational factors into improved performance. These findings highlight the multifaceted nature of human capital management. To optimize employee performance, organizations like Hotel Grandhika Pemuda Semarang should prioritize fostering a positive organizational culture, nurturing employee motivation, and cultivating a sense of job satisfaction among their workforce.